Problems of improvement of the legislation on economic security and tasks to support entrepreneurship and development of digital economy in the Republic of Uzbekistan - Makhmutkhodjaeva, Luiza; Arkhangelskaya, Elena (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
In the article there considered problems of improving legal regulation of economic security, pandemic response, urgent issues of the development of digital economy, creating legal framework necessary to regulate the use of modern digital technologies in economic sectors, and further growth of entrepreneurial activity. Specific tasks have beenidentified, the solution of which will create the necessary conditions for the formation of full value digital environment in the Republic of Uzbekistan, and it will certainly allow the country to resolve the issue of global competitiveness as soon as possible, and contribute to strengthening economic security of the Republic